Magnetic resonance imaging of hip joint cartilage and labrum - Zilkens, Christoph (PAGEPress Publications, 2011)
Hip joint instability and impingement are the most common biomechanical risk factors that put the hip joint at risk to develop premature osteoarthritis. Several surgical procedures like periacetabular osteotomy for hip dysplasia or hip arthroscopy or safe surgical hip dislocation for femoroacetabular impingement aim at restoring the hip anatomy. However, the success of joint preserving surgical procedures is limited by the amount of pre-existing cartilage damage. Biochemically sensitive MRI techniques like delayed Gadolinium Enhanced MRI of Cartilage (dGEMRIC) might help to monitor the effect of surgical or non-surgical procedures in the effort to halt or even reverse joint damage.